Age-specific associations with dental caries in HIV-infected, exposed but uninfected and HIV-unexposed uninfected children in Nigeria - Paul Akhigbe; Nneka M. Chukwumah; Morenike Oluwatoyin Folayan; Kimon Divaris; Ozoemene Obuekwe; Augustine Omoigberale; Elima Jedy-Agba; Michael Kim; Manhattan E. Charurat; Vincent P. Richards; Modupe O. Coker (BMC, 2022)
Abstract Background HIV infection and its management confer a substantial health burden to affected individuals and have been associated with increased risk of oral and dental diseases. In this study, we sought to quantify HIV-associated differences in the prevalence and severity of dental caries in the primary and permanent dentition of 4-11-year-old Nigerian Children. Methods We used clinical, laboratory, demographic, and behavioral data obtained from an ongoing cohort study of age-matched HIV-infected (HI, n = 181), HIV-exposed-but-uninfected (HEU, n = 177), and HIV-unexposed-and-uninfected (HUU, n = 186) children. Measures of dental caries experience (i.e., prevalence and severity) were based on dmft/DMFT indices recorded by trained and calibrated clinical examiners. Differences in primary and permanent dentition caries experience between HI, HEU, and HUU were estimated using multivariable logistic and negative binomial regression modeling. Results HI children had significantly higher caries experience (33%) compared to HEU (15%) and HUU (22%) children. This difference persisted in fully adjusted analyses [odds ratio (OR) = 1.6; 95% confidence interval (CI) = 1.0-2.6], was most pronounced in the permanent dentition (OR = 3.4; 95% CI = 1.2-9.5), and mirrored differences in caries severity. While molars were predominantly affected in both primary and permanent dentitions, caries lesion patterns differed between dentitions. Caries severity was significantly associated with hypoplastic primary teeth, gingival inflammation, and lower CD4 counts. Conclusions We found that the higher prevalence and severity of dental caries among HI children was driven by increased burden of permanent dentition caries compared to their uninfected counterparts. The dentition-specific associations identified in this study highlight the need to design and implement age-specific caries prevention strategies. These may include intensified oral hygiene regimens aimed at mitigating the cariogenic impact of hyposalivation among HI children. Similarly, the long-lasting impacts of developmental defects of the enamel in the primary and permanent dentitions must not be ignored.